The Improving Fine Motor Skills in 4-5 Year Old Children Through Paper Cutting and Folding Media Activities at Bhaktiwati Kindergarten, Surabaya - Eni Lianah; dwi jayanti kurnia; Salma Aulia Khosibah (Journal of Art and Creativity in Early Childhood Education, 2025)
This study was motivated by the limited fine motor skills of 4–5-year-old children in cutting folded paper, partly due to teachers’ greater emphasis on student worksheets, which reduced engagement in hands-on activities. This classroom action research aimed to improve children’s fine motor skills through folded paper cutting activities. The study involved 10 children aged 4 5 years at TK Bhaktiwati, Sukomanunggal District, Surabaya, conducted from December 2024 to January 2025. The research applied the Kemmis and McTaggart model, consisting of two cycles, each including planning, action, observation, and reflection. Data were collected using observation sheets focusing on children’s ability to hold scissors correctly, follow cutting lines, and complete tasks independently. The findings showed a consistent increase in cutting skills. The pre-cycle average score was 45% (5 children), which improved to 64.64% (7 children) in Cycle I. In Cycle II, the incorporation of smile card rewards made activities more engaging, resulting in increased mastery to 86.66% (9 children). Since the indicators were met in Cycle II, the research was completed. These results indicate that the use of demonstration methods combined with folded paper cutting activities positively enhances children’s fine motor development and engagement in learning.